Assessment of the Relationships Between Spinopelvic Radiologic Parameters and Balance, Gait and Falls Efficacy in Patients with Postmenopausal Osteoporosis - AKYÜZ, GÜLSEREN DERYA (GALENOS YAYINCILIK, 2018)
Objective: The aim of this study is to investigate the relationship between sagittal balance, spinopelvic parameters, bone mineral density, balance, and falls efficacy in postmenopausal osteoporosis patients. Materials and Methods: Forty patients between the ages of 40-80 with a diagnosis of postmenopausal osteoporosis were included in the study. Spinopelvic parameters (sagittal vertical axis (SVA), thoracic kyphosis, lumbar lordosis, pelvic tilt, pelvic incidence, sacral slope) were calculated from spine radiographs. Patients were applied Tinetti Balance and Gait Assessment and Falls Efficacy Scale. Relationship between bone mineral density measurements, clinical parameters, spinopelvic parameters, balance and gait, and falls efficacy were investigated. Results: Mean age of the patients was 63.42 +/- 8.98 and the mean L1-L4 T score was 2.5 +/- 0.68. Statistically significant negative correlation was found between the L1-L4 and L2-L4 vertebrae bone mineral density and T score, and sacral slope. Negative statistical correlations were found between SVA and Tinetti Balance and Gait Assessment balance subtest and total scores. There was no statistically significant relationship with other spinopelvic parameters. There was no significant correlation between SVA and spinopelvic parameters and Falls Efficacy Scale, while a statistically significant negative correlation detected between Falls Efficacy Scale and Tinetti Balance and Gait Assessment balance and gait subtests and total scores. Among the patients with normal, mild and severe deformity sagittal balance, there was statistically significant difference in terms of Tinetti Balance and Gait Assessment balance and gait subtests scores and total scores, while there was no difference with regards to Falls Efficacy Scale. Conclusion: In postmenopausal women with osteoporosis, SVA, sagittal balance parameters, and balance and gait functions were found to be associated.
Keywords: Balance; osteoporosis; thoracic kyphosis; sagittal spinal balance; spinopelvic parameters; SAGITTAL BALANCE; VERTEBRAL FRACTURE; VALIDATION; ALIGNMENT